Effect of Organic Acids and Probiotics on Salmonella enteritidis Infection in Broiler Chickens - Wolfenden, A.D.; Vicente, J.L.; Higgins, J.P.; Filho, R.L. Andreatti; Higgins, S.E.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
The effect of an organic acid mixture (OA) and a Lactobacillus-based probiotic culture on Salmonella enteritidis (SE) infection in broiler chicks was evaluated. In exp. 1, chicks were challenged by oral gavage with SE, held in chick boxes for 2 h and randomly assigned to either untreated control or continuous OA treatment in the drinking water. Crop and cecal tonsils were cultured at 48 h and 5 d post-challenge for recovery of SE. Recovery of SE in the crop and cecal tonsils at 48 h was significantly (p